Derivational Morphology Features in Common Akeanon Dialects - Biray, Ersyl (International Journal of Language and Literary Studies, 2023)
Akeanon language reflects the rich cultural uniqueness of Aklan natives in Panay Island, Philippines. It is spoken in different dialects as Akeanon Buruangganon, Akeanon Nabasnon, and Akeanon Bukidnon distinct from the standard Akeanon used in the central town of Kalibo. This descriptive cross-sectional study used documentary and content analyses to determine the derivational morphology features, and the different variations of common Akeanon dialects in terms of structure, word order, and affixation. Results revealed that most dialect variations of the language are expressed with endearment and warmth, with respect and assurance; followed by an inverted pattern from the normal word order of spoken or written English. Reduplication of base words and affixations using circumfix or confix were noted. Most of these affixes were derivational morphemes. Structure variations were observed wherein a bound morpheme in one dialect changes in another; some dropped an affix but retained its definition. Some Akeanon dialects have Tagalog origin while standard Akeanon words have substitutes in Akeanon dialect variations.